Maritime Tribunal as Quasi-Judicial Body in Indonesia - Ghalib Alghani Lusarno (Jurnal Penelitian Transportasi Laut, 2022)
Maritime Tribunal as Quasi-Judicial Body in Indonesia; Supreme Court is a judicative body under Article 24 of the 1945 Constitution 1945. The development of the legal system in Indonesia has established new institutions with judicative power to settle certain disputes which are attributed from the special legislation. In the field of maritime law in Indonesia, the Maritime Tribunal has the authority to conduct further examination of a shipwreck in accordance with the Shipping Law. This article uses the normative legal research method with the statutory statute approach. This matter requires further analysis towards the legality of the Maritime Tribunal's authority in Indonesia, that the tribunal is part of the an echelon II organ of the Ministry of Transportation. Based on the criteria and characteristics of a quasi-judicial body, Maritime Tribunal is a quasi-judicial body that possessed has mixed authority of executive function in implementing rules and regulation and administration in the maritime sector, as well as nd judicative function to conduct legal process concerning shipwrecks, that the result of the examination becomes the consideration of the judge in general courts to issue the judgment. The judge in civil or criminal disputes that arise from shipwrecks, in making consideration of the judgment, oblige the disputing parties to settle further examination of a shipwreck in Maritime Tribunal.